1997
DOI: 10.1038/sj.bjp.0701437
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between the endothelial cell‐derived contracting factors prostacyclin and angiotensin II and nitric oxide/cyclic GMP in human primary varicosis

Abstract: 1 The role of the endothelium in the vasomotor control of human veins in the lower extremity is little understood. We tested the hypothesis that the production of relaxing and contracting factors is altered in endothelial cells from varicose saphenous veins which may predispose to the decreased vessel tone observed in primary varicosis. 2 We determined the intracellular accumulation of guanosine 3':5'-cyclic monophosphate cyclic GMP; a measure of nitric oxide production) and the release of endothelin and prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…In addition, activated endothelial cells release growth factors that induce smooth muscle cell migration, proliferation and de-differentiation into the synthetic phenotype, leading to the formation of neointima [26]. Histology analysis showed that endothelial cells from varicose veins had the reduced endothelin-1 binding and endothelin-B receptor density as well as reduced production of the endothelial cell-derived contracting factors prostacyclin and angiotensin II, which may be partially responsible for the reduced vasocontractility in varicose veins [27,28]. Matrix metalloproteinases (MMPs) and their inhibitors, tissue inhibitors of metalloproteinases (TIMPs), regulate and maintain the extracellular matrix.…”
Section: Alteration In Matrix Proteins In Varicose Veinsmentioning
confidence: 99%
“…In addition, activated endothelial cells release growth factors that induce smooth muscle cell migration, proliferation and de-differentiation into the synthetic phenotype, leading to the formation of neointima [26]. Histology analysis showed that endothelial cells from varicose veins had the reduced endothelin-1 binding and endothelin-B receptor density as well as reduced production of the endothelial cell-derived contracting factors prostacyclin and angiotensin II, which may be partially responsible for the reduced vasocontractility in varicose veins [27,28]. Matrix metalloproteinases (MMPs) and their inhibitors, tissue inhibitors of metalloproteinases (TIMPs), regulate and maintain the extracellular matrix.…”
Section: Alteration In Matrix Proteins In Varicose Veinsmentioning
confidence: 99%
“…Although the reduced AngII responsiveness could be due to localized alterations in VarV, it could also be a component of a more generalized change in the renin-angiotensin system and its effects on the venous system. This is supported by reports that the renin-angiotensin system is suppressed and that the circulating levels of AngII are reduced in the plasma of patients with VarV 30. It is possible that in the presence of a decreased responsiveness to AngII, a maintained response to PHE may represent a compensatory mechanism to maintain venous tone against the increased venous pressure associated with VarV.…”
Section: Discussionmentioning
confidence: 69%
“…The hypothesis of a defective smooth muscle tone is supported by clinical observations and experimental studies in which varicose veins showed a reduced ability to contract in response to several vasoconstrictors including α‐adrenoceptor agonists and endothelin [9–11]. The possible role of an imbalance between endothelium‐derived contracting and relaxing factors was reported by our group [12].…”
Section: Introductionmentioning
confidence: 82%